Does Audit Quality Strengthen the Impact of ESG Disclosure on Earnings Management? Empirical Evidence - Edi Triwibowo; Erlina Widayanti; Thofa Hanif Aditya (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The increasing adoption of Environmental, Social, and Governance (ESG) disclosure has intensified academic and professional interest in its role in enhancing financial reporting quality. Nevertheless, empirical evidence regarding the relationship between ESG disclosure and earnings management remains inconclusive, suggesting that additional governance mechanisms may influence this relationship. This study investigates the effect of ESG disclosure on earnings management and examines whether audit quality strengthens this relationship. The study employs a quantitative explanatory research design using panel data from non-financial companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2025 period. The sample is selected using purposive sampling based on data availability and reporting consistency. Panel data regression with moderated regression analysis is employed to test the direct and moderating effects, while firm size, leverage, profitability, and firm age are included as control variables. The findings indicate that ESG disclosure significantly reduces earnings management, suggesting that firms with more comprehensive sustainability disclosure exhibit higher financial reporting quality. Furthermore, audit quality strengthens the negative relationship between ESG disclosure and earnings management, indicating that high-quality external audits enhance the credibility of sustainability reporting and limit managerial opportunistic behavior. These findings contribute to the literature on corporate governance and sustainability reporting while providing practical implications for regulators, investors, auditors, and corporate managers seeking to improve reporting transparency and accountability.